2009
DOI: 10.1016/j.bbrc.2009.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Leptin regulates tau phosphorylation and amyloid through AMPK in neuronal cells

Abstract: Leptin, which serves as a lipid-modulating hormone to control metabolic energy availability, is decreased in Alzheimer's disease (AD) patients, and serum levels are inversely correlated to severity of dementia. We have previously described the effects of leptin in reducing amyloid β protein both in vitro and in vivo, and tau phosphorylation in vitro. Herein, we systematically investigated the signaling pathways activated by leptin, leading to these molecular endpoints, to better understand its mechanism of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 38 publications
3
131
0
1
Order By: Relevance
“…Numerous studies have highlighted the important role of AMPK in the pathogenesis of Alzheimer's disease, which is characterized by cognitive impairment (22,23). An in vitro study by Greco et al (24) showed that leptin increased cellular metabolism by activating AMPK to reduce Aβ expression in neurons. A different study also performed by this group (25) demonstrated that leptin directly regulated Aβ through the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the important role of AMPK in the pathogenesis of Alzheimer's disease, which is characterized by cognitive impairment (22,23). An in vitro study by Greco et al (24) showed that leptin increased cellular metabolism by activating AMPK to reduce Aβ expression in neurons. A different study also performed by this group (25) demonstrated that leptin directly regulated Aβ through the AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…67 In addition, leptin-induced AMPK activation is associated with a reduction in Tau phosphorylation. 75 Despite these findings, other evidence sustains an opposite role for AMPK in AD. Interestingly, the activation of AMPK by metformin is protective in females but increases memory dysfunction in males, suggesting a sex-divergent cognitive effect in a murine model of AD.…”
Section: Ampk In Admentioning
confidence: 99%
“…However, the brain (mostly hypothalamus) is not the only target for leptin and other adipokines, as well as the food intake is not the only biological e ect of these adipokines. Rather, some adipokines support various metabolic and cognitive functions and exert both metabo-and neurotrophic actions (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Current data of adipose-derived neuroendocrine and neurotrophic factors are summarized in Tables 1, 2.…”
Section: Adipobiology 7 2015mentioning
confidence: 99%